2006
DOI: 10.1016/j.febslet.2006.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Normal acute and chronic inflammatory responses in sphingosine kinase 1 knockout mice

Abstract: Sphingosine-1-phosophate, generated from the phosphorylation of sphingosine by sphingosine kinase enzymes, is suggested to function as an intracellular second messenger for inflammatory mediators, including formyl peptide, C5a, and Fc. More recently, a role for sphingosine kinases during inflammation has also been proposed. Here we show that sphingosine kinase 1 knockout mice exhibit normal inflammatory cell recruitment during thioglycollate-induced peritonitis and that sphingosine kinase 1-null neutrophils re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 32 publications
2
58
1
Order By: Relevance
“…SphK1 expression is increased in human IBD colons, and SphK1-deficient mice are protected from IBD pathology (14). These are in contrast to data generated from models of thioglycollate-induced peritonitis and CIA, where SphK1 knockout mice exhibit normal acute and chronic inflammatory responses (31). It is possible that mice lacking the SphK1 gene during embryonic development may be adapted not to rely on this pathway for inflammatory responses postnatally.…”
Section: Discussioncontrasting
confidence: 52%
“…SphK1 expression is increased in human IBD colons, and SphK1-deficient mice are protected from IBD pathology (14). These are in contrast to data generated from models of thioglycollate-induced peritonitis and CIA, where SphK1 knockout mice exhibit normal acute and chronic inflammatory responses (31). It is possible that mice lacking the SphK1 gene during embryonic development may be adapted not to rely on this pathway for inflammatory responses postnatally.…”
Section: Discussioncontrasting
confidence: 52%
“…administration of SphK1 siRNA significantly reduced both incidence and disease severity in the development of murine CIA. Recently, it was suggested that SphK1 knockout mice developed CIA with normal incidence and severity (47). It is possible that mice lacking the SphK1 gene during embryonic development may be adapted to not rely on this pathway for inflammatory responses postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Zemann et al (2006) reported that serum S1P levels in SK-2-deficient mice increased, but decreased by approximately 50% in SK-1-deficient mice. Moreover, Michaud et al (2006) measured S1P levels in forepaw tissue and found only slight decreases in SK-1-deficient mice. Recently, Mizugishi et al (2007) generated SphK1 -/-SphK2 q/-mice and investigated uterine decidualisation.…”
Section: Discussionmentioning
confidence: 99%